Increasing Youth Capacity Through Language Workshops and Agricultural Business Skills to Increase Family Income - Amron Zarkasih Ritonga; Maimunah Ritonga; Joni Rianto; Rini Antika Ritonga (Saniya Institute, 2024)
The program